Pengaruh perasan rimpang temu putih terhadap ketoksikan akut dan toksiko kinetika teofilin pada tikus = Effectivity Sequeezing of White Turmeric on Interfearing Toxicokinetics and Acute Toxicity of Theophylline - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT The interaction between theophylline and sequeezing of white turmeric rhizome was studied to understand ultimate result of interaction or toxicological effect. The fresh rhizome were washed, blended, sequeezed and dried with freeze dried to get dry sequeez. In order to study acute toxicity, fifty male Wistar rats were divided randomly into five groups of ten animals. To the rats of control group, oral theophylline (300 mg/kg bw in CMC 1%) were administered orally. The animals in the treatment groups were given by sequeeze of white turmeric 15,75 (P-l)